Islam Kebangsaan Inklusif Formulasi Gagasan Islam Rahmat Lil 'Alamin dan Bhinneka Tunggal Ika - Alfanny, M. Sa'ad; Yusuf, Kamal; Daud, Fathonah K. (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2025)
The era of globalisation has changed the way Indonesian society perceives the relationship between Islam and nationality. The flow of global information has expanded intercultural interactions but has also given rise to political polarisation, digital tribalism, and a crisis of social tolerance. This study, through a descriptive-reflective approach, seeks to reformulate the relevance of integrating the Islamic value of Raḥmatan li al-‘Ālamīn and the spirit of Bhinneka Tunggal Ika as an ethical paradigm in responding to the challenges of contemporary plurality. The results of the study gave birth to the concept of Inclusive National Islam, a religious paradigm that places compassion, justice, and universal humanity at the core of national morality. In socio-political practice, this idea is realised through a movement of religious moderation and the development of an ecosystem of moderation that fosters dialogue, critical reflection, and national solidarity. Thus, Inclusive National Islam is not only a conceptual offering but also a practical model that strengthens social cohesion and reinforces Indonesian civilisation rooted in Islamic spirituality and the spirit of diversity.